A facile coprecipitation method to synthesize FexOy/Fe decorated graphite sheets with enhanced microwave absorption properties. (20th February 2019) - Meng, Rui; Zhang, Tao; Yu, Haijing; Zhang, Jian; Wen, Guangwu; Huang, Xiaoxiao; Huang, Longnan; Xia, Long; Zhong, Bo
Abstract: Fex Oy /Fe decorated graphite sheets (DGS) are synthesized using a facile coprecipitation method followed by heat treatment under different conditions. The size and chemical composition of the particles loaded on graphite sheets can be tailored by adjusting the heat treatment temperature and atmosphere. The obtained α -Fe2 O3 DGS (S1 ), Fe3 O4 DGS (S2 and S3 ), and Fe DGS (S4 ) all exhibit excellent electromagnetic (EM) wave absorption when compared with conventional graphite/magnetic-particle composites. The minimum reflection loss (RL) can reach −42.1 dB at 4.16 GHz in the S2 /paraffin composites. The bandwidth of the RL below −10 dB covers 4.4 GHz (11.04–15.44 GHz) with a thickness of 2 mm. A possible EM wave loss mechanism has been proposed in detail. The multiple absorbing mechanisms could control the excellent absorption, resulting in a product with a feasible application in stealth materials.